Pengaruh Temperatur Substrat Dan Waktu Deposisi Menggunakan Metode Spray Pyrolysis Terhadap Morfologi, Struktur Kristal Dan Sifat Listrik Lapisan Tipis Zno - Arnanda, Febri (Jurnal Furnace, 2019)
Transparent Conducting Oxide (TCO) is a Transparent conductor that functions as a low-e windows and transparent front electrode. TCO material has the characteristics of low electrical resistivity and high transparency, the TCO made in this study is a Zinc Oxide (ZnO) material. Process variables used in this study include substrate temperature and deposition time. Making ZnO thin films using the spray pyrolysis (Ultrasonic Nebulizer) method. Characterization used in ZnO thin layer samples includes Scanning Electron Microscopy-Energy Dispersion (SEM-EDS), X-ray Diffraction (XRD) and I-V Meter (picoammeter). The results showed that the morphology of the ZnO thin layer had been formed fairly evenly on the surface of the glass substrate at a temperature of 500C deposition time of 20 minutes and 1000C at the deposition time of 30 minutes. The higher the temperature of the ZnO thin layer does not form on the surface of the glass substrate. The longer the deposition time of 30 minutes the peak intensity is getting better. ZnO thin layer shows hexagonal structure, intensity of dominant peak at orientation (011), ZnO thin layer resistivity temperature 500C 5.6 x 10-10 Ω.cm and temperature 1000C 2.69 x 10-10 Ω.cm.